An Introduction to the Boltzmann Equation and Transport Processes in Gases - Kremer, Gilberto Medeiros; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book deals with the classical kinetic theory of gases. Its aim is to present the basic principles of this theory within an elementary framework and from a more rigorous approach based on the Boltzmann equation. The subjects are presented in a self-contained manner such that the readers can understand and learn some methods used in the kinetic theory of gases in order to investigate the Boltzmann equation. It is expected that this book could be useful as a textbook for students and researchers who are interested in the principles of the Boltzmann equation and in the methods used in the kinetic theory of gases.
Basic Principles of the Kinetic Theory -- The Boltzmann Equation -- The Chapman-Enskog Method -- Moment Methods -- Polyatomic Gases -- Dense Gases -- Granular Gases -- Mixtures of Monatomic Gases -- Chemically Reacting Gas Mixtures.
Keywords: Engineering; Mathematics; Mechanics, applied; Engineering; Theoretical and Applied Mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Applications of Mathematics; Classical Continuum Physics